Characteristics of Society in Education - Eti Robiatul Adawiah; Moh Jailani; Cecep Hilman (P3M IAI Nusantara Batang Hari, 2023)
The characteristics of society in education are strongly influenced by various aspects. Among these are social, economic, cultural, legal, and political. These aspects greatly affect the characteristics of society in Education. The purpose of writing this article is to determine the correlation of social, economic, cultural, hukm and political conditions to the characteristics of society in education. The writing of this article uses qualitative methods with a descriptive approach and data collection techniques in the form of literature studies. The results of the study show that the conditions of social affairs, economics, culture, law, and politics exert a major influence on the characteristics of society in education. Therefore, it is important for us as actors in the world of Education to consider the characteristics of the community when designing education policies and developing programs according to the conditions of the community.